THE RIGHT TO LEGAL REPRESENTATION WHEN APPEARING BEFORE A DISCIPLINARY ENQUIRY Hamata v Chairperson, Peninsula Technikon Internal Disciplinary Committee 2002 7 BCLR 756 (SCA) - Glynis van der Walt; Adriaan van der Walt (Obiter, 2022)
Given the present work climate in South Africa, it can no longer be assumed that after completing tertiary education, a graduate is automatically assured of employment in his or her field of study. Opportunities are scarce and the supply generally outweighs the demand. It is therefore no surprise that any future candidate for the job market would prefer to keep his or her education record clean. The possible consequences of a disciplinary enquiry have the potential to impact on the record of the student concerned. Such a student will put up the strongest possible defence at such an enquiry, and the question arises as to whether or not the student should be entitled to acquire the services of a legal representative to serve his or her best interests. At the same time, seen from the viewpoint of a tertiary institution, the preference may well be to keep the enquiry a domestic affair and not allow the intervention of an outsider who may cause the enquiry to be prolonged, or show the chairperson or initiator of the enquiry, often a layperson, to be inadequately skilled when compared with a legal practitioner. The question of the right to representation at a disciplinary enquiry of an employee arises for similar reasons, and it happens more often. In the present constitutional dispensation it cannot be assumed that the right to legal representation at disciplinary enquiries is only established by contractual agreement (individual or collective), or by an express provision in some legislative enactment, or even that such agreement or enactment may lawfully prohibit legal representation at enquiries. In the recent judgment in Hamata v Chairperson, Peninsula Technikon Internal Disciplinary Committee (supra; hereinafter “Hamata”) handed down by the Supreme Court of Appeal this issue of legal representation at disciplinary enquiries was considered and addressed.